Barosinusitis Pada Penyelam : Tinjauan Pustaka Barosinusitis In Divers : Literatur Review - Ratna Tanzilla Chaerunnisa Hipi (Fakultas Ilmu Kesehatan Universitas Gresik, 2023)
Indonesia is an archipelagic country that has about 17,508 islands spread from Sabang to Merauke and 70% of its territory is covered by the ocean. The Indonesian sea has an abundant diversity of natural resources so that it is used as the main source of livelihood for most coastal or archipelagic communities, namely as traditional fishermen with the majority as traditional divers, transportation routes, and recreational tourism objects and sports under the water in the form of scuba diving which has recently been in great demand. This diving activity by traditional fishermen and scuba divers has a high risk of work accidents so it must be a special concern to prevent barosinusitis. Barosinusitis can occur due to lack of knowledge regarding the risks of diving and procedures for using diving equipment, incomplete and unsafe equipment used, and diving activities carried out not in accordance with predetermined diving procedures